Sustainability indicators in energy corporations: an evaluation with Brazilian companies (Research, Society and Development, 2022)
The installation process of undertakings with potential impact on the environment changes environmental and socio-cultural scenarios, generating positive and negative situations for the municipalities and communities where they are located. The search for new economic and technological models, given the growing demands and pressures of society in relation to environmental conservation, imposed a new challenge for corporations: to be competitive and sustainable at the same time. Therefore, this study aimed to descriptively evaluate the understanding and applicability of the sustainability indicators contained in the Global Report Initiative (GRI) Sustainability reports in three companies in the energy sector with facilities in the Amazon Basin. For this purpose, 22 indicators contained in the GRI reports were selected and evaluated. The results show that corporations have adapted to new market requirements, evidencing concern with social, environmental and economic issues, as well as their interaction to obtain sustainable processes through the continuous improvement of their plans and actions, since they apply the rules of the GRI, providing access to the population on the collected data, making it possible for them to know about the programs and projects in progress and to be able to charge for responsible socio-environmental actions.